농촌 지역사회의 변화 동향과 전망 - 박대식 (한국농촌경제연구원, 2003)
Trend and Prospect of Rural Community Change: Centered around the Change of Population Structure The main purposes of this study are as follows: 1) to investigate the trend of rural community change; and 2) to suggest the prospect of rural community change, centered around the change of population structure. The major research methods of this study include collection of existing related data, the E-mail(or telephone) survey, and the field survey. The collection of existing related data was conducted by investigating the data of related governmental organizations and research institutes. The E-mail(or telephone) survey was conducted by forty experts in order to collect the opinions of rural community change related specialists. The field survey was carried out fargeting the residents of 3 villages to identify the trend of rural community change. Descriptive statistics such as frequency, percentage, and mean were used to organize and summarize the data of E-mail and field survey. The major findings of this study are as follows: 1) the decreasing trend of rural population may be weakened or stabilized; 2) the proportion of single or a couple family may be increased; 3) the number of social organizations in rural villages may be decreased greatly; 4) the proportion of consignment farming may be increased more; and 5) the pattern of rural community change may become different depending on the various circumstances of the communiles. Researchers: Park Dae-Shik and Park Kyong-Cheol E-mail Address: pds8382@krei.re.kr
Keywords: 농촌인구; 인구변화; 인구구조